Implementasi Principal Component Analysis dalam Analisis Faktor Kecacingan pada Anak Sekolah Dasar di Kabupaten Jember - Nur Muhammad Ali Al Faizi; Mursyidul Ibad; Kuuni Ulfah Naila El Muna; Budhi Setianto (Yayasan Literasi Sains Indonesia, 2023)
Despite a decrease from 2021 to 2022 based on data from the Indonesian Nutrition Status Survey in 2023, helminthiasis remains a major problem in Indonesia, with high prevalence rates in 2020. The Indonesian government has intervened to address the problem, including a survey to assess helminthiasis prevalence in Jember district conducted by BBTKLPP Surabaya and Jember District Health Office. The survey results showed that some students were still infected with helminthiasis, and there were problems with clean and healthy living behavior in some students. However, there are difficulties in presenting sensitive reports, so 13 indicators in the questionnaire were simplified using PCA (Principal Component Analysis) method to facilitate data visualization and analysis given the correlation among indicators. This study used a descriptive observational design with a cross-sectional approach and included 190 samples of primary school students out of a total of 615 samples. Some samples were not used because of incomplete or blank data due to absence at the time of the survey. The results showed that 7 out of 13 indicators were feasible for further testing, while the remaining 6 indicators were not feasible. Using the PCA method, 3 indicators (Principal Component) were successfully obtained to represent the other 7 indicators, namely basic knowledge of helminthiasis, environmental sanitation, and personal hygiene related to helminthiasis among primary school children. This study concluded that the PCA method is effective in identifying factors associated with helminthiasis and can reduce correlated variables without losing important information from the original data. This helps in the implementation of helminthiasis prevention efforts in Indonesia.